If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = 3x + -15 Reorder the terms: 3 = -15 + 3x Solving 3 = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + -3x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + -3x = -15 + 0 3 + -3x = -15 Add '-3' to each side of the equation. 3 + -3 + -3x = -15 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = -15 + -3 -3x = -15 + -3 Combine like terms: -15 + -3 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| 2x+50=12x-10 | | -63+46w=25w-147 | | 7/c-2/c=4/c-1 | | z^2-5iz-4=0 | | 15/2p-13/2p | | 23h-89=63+42h | | 5ln(4x-2)-16=9 | | x^4+11x^3-44=0 | | 16x-19=113-6xz | | 63d-44=-140+47d | | 3x^2+x-1900=0 | | 63d-44=140+47d | | -21+6x=33+9x | | 12-3x/x^2-8x+16 | | 5(g-2)+g=6g-24 | | x=log(3)15 | | x^4+11x^2-44=0 | | x^2+11x^2-44=0 | | 14j-53=73+32j | | 2n/n^2-3n | | -14p+51=57p+23 | | t-1/t^2+t | | 75+21k=19+29k | | -80=b-91 | | x(7-x)+2whenx=-4 | | 20=t-70 | | 4(x+8)-7whenx=8 | | lg(x+3)+lg(1-x)=lg(4x+8) | | v-4.7=23.8 | | 59+19f=8f+5 | | k-16=7 | | 15=c-40 |